Ethnic, geographical and altitude considerations and maternal mortality associated with HELLP syndrome in Ecuador: a population-based cohort study - Marco Coral-Almeida; María Eugenia Sánchez; Aquiles R. Henríquez-Trujillo; María Barriga-Burgos; Evelyn Alarcón-Moyano; Eduardo Tejera (BMC, 2024)
Abstract Background Eclampsia and pre-eclampsia rank as the third leading causes of maternal death in Ecuador, following pre-existing chronic diseases and postpartum haemorrhage, as reported by the Ecuadorian National Institute of Statistics and Census (INEC). In contrast, HELLP (Haemolysis, Elevated Liver enzymes, Low Platelet count) syndrome remains underexplored epidemiologically, not only in Latin America but globally. This study marks the first population-based investigation into HELLP syndrome incidence and mortality in Ecuador, examining geographical variations, altitude influences and ethnic backgrounds. Methods Conducted as a retrospective population-based cohort study from 2015 to 2017, this research delves into the incidence, risk factors and maternal mortality associated with HELLP syndrome in Ecuador. Utilising data from INEC and the Ecuadorian Ministry of Health, we identified HELLP syndrome cases through ICD-10 (International Classification of Diseases, tenth revision) coding in hospitalised individuals. Logistic regression analysis was employed to explore association, whilst geospatial statistical analysis focused on cantons to identify significant spatial clusters. Primary outcome measures include HELLP syndrome incidence and maternal mortality, supplying crucial insights into the syndrome's impact on maternal health in Ecuador. Results The incidence of HELLP syndrome is 0.76 (0.69-0.84)/ 1000 deliveries. Afro-Ecuadorian communities have a higher risk (Odds Ratio (OR) = 2.18 (1.03-4.63)) compared to Indigenous Ecuadorian communities. Living at mid-level or high altitude is a significant risk factor OR of 2.79 (2.19-3.55) and an OR 3.61 (2.58-5.03), respectively. Being an older mother was also identified as a risk factor. Women living more than 20 km from the obstetric unit have an OR of 2.55 (2.05-3.18). Moreover, we found that cantons with higher crude HELLP syndrome incidence also have lower numbers of physicians (R = 0.503, p-value < 0.001). The mortality incidence of women with HELLP syndrome is 21.22 (12.05-20.59)/1000 deliveries with HELLP syndrome diagnoses. Conclusions High altitude, advanced maternal age and geographical distance between residence and health centres are risk factors for HELLP syndrome. Maternal mortality in women with HELLP syndrome is higher than pre-eclampsia and eclampsia but comparable with previous reports in other countries.